Composite with TiO2 and extension of discharge voltage range for capacity enhancement of a Li4Ti5O12 battery. Issue 69 (12th September 2017) - Ding, Meng; Liu, Hui; Zhao, Xiangnan; Pang, Lingyan; Deng, Lu; Li, Mengyan
Abstract : Herein, nanosheet-assembled Li4 Ti5 O12 –TiO2 (LTO–TiO2 ) microspheres were successfully obtained via a hydrothermal method. Abstract : Herein, nanosheet-assembled Li4 Ti5 O12 –TiO2 (LTO–TiO2 ) microspheres were successfully obtained via a hydrothermal method. The structure and morphology of the composite were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Subsequently, the electrochemical performance of the product was determined by an electrochemical workstation and a LAND CT2001A (Land, China) battery testing system. The experimental results demonstrated that both the formation of a composite with anatase TiO2 and the extension of the discharge voltage range were beneficial for the enhancement of the specific capacity of Li4 Ti5 O12 . When the discharge cut-off voltage was decreased to 0 V, the LTO–TiO2 composites exhibited a higher discharge specific capacity of 411.3 mA h g −1 during the first cycle in comparison with pure LTO, which was mainly attributed to the intercalation of more lithium ions into the LTO–TiO2 composites at a low potential (<1.0 V). Moreover, owing to the introduction of anatase TiO2, the Li + charge/discharge process at a higher potential of around 2.0 V ( vs. Li/Li + ) was also favorable for the enhancement of the capacity of LTO composites and their applied voltage range. In addition, the LTO–TiO2 composites exhibited high electronic conductivity and lithium ion diffusion coefficients and excellent coulombic efficiency.